Highly Commended Paper - Markou, George (My University, 2026)
Highly Commended Paper, Title: A simplified and efficient hybrid finite element model (HYMOD) for non-linear 3D simulation of RC structures, Engineering Computations, Emerald LiteratiNetwork, August 2016.
Keywords: Sciences